2021
DOI: 10.22541/au.161101907.70798763/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A high-quality carabid genome provides insights into beetle genome evolution and cold adaptation

Abstract: The hyper-diverse order Coleoptera comprises a staggering ~25% of known species on Earth. Despite recent breakthroughs in next generation sequencing, there remains a limited representation of beetle diversity in assembled genomes. Most notably, the ground beetle family Carabidae, comprising more than 40,000 described species, has not been studied in a comparative genomics framework using whole genome data. Here we generate a high-quality genome assembly for Nebria riversi, to examine sources of novelty in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 104 publications
(120 reference statements)
0
2
0
Order By: Relevance
“…The origin of alpine endemic insects has complex drivers (Queiroz et al 2022), including allopatric speciation (Schoville and Roderick, 2010, Schat et al 2022, Todisco et al 2010), diversity dependent radiation (Condamine 2018), or interactions with endosymbionts (Lucek et al 2021, Weng et al 2021). We fill in new information into the mosaic describing diversification drivers of alpine insects in relation to the role of the evolution of their climatic niches.…”
Section: Discussionmentioning
confidence: 99%
“…The origin of alpine endemic insects has complex drivers (Queiroz et al 2022), including allopatric speciation (Schoville and Roderick, 2010, Schat et al 2022, Todisco et al 2010), diversity dependent radiation (Condamine 2018), or interactions with endosymbionts (Lucek et al 2021, Weng et al 2021). We fill in new information into the mosaic describing diversification drivers of alpine insects in relation to the role of the evolution of their climatic niches.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the results of both transcriptome and metabolome analyses showed that propanoate metabolism pathways were induced by sewage treatment and key genes related to propanoate metabolism (Table S5). Furthermore, the downregulated metabolite was 2-oxobutanoate (2-OBA), which as a toxic metabolic intermediate, generally arrests the cell growth of most microorganisms and blocks the biosynthesis of target metabolites [35-36]. In the wastewater treatment process, the metabolite of 2-OBA is downregulated, which can promote the effect of microalgae on wastewater treatment and maintain the normal metabolism of microalgae.…”
Section: Discussionmentioning
confidence: 99%